KOMPETENSI GURU DALAM PEMBELAJARAN - Muhammad Rifai Harahap (Yayasan Literasi Kita Indonesia, 2020)
Nowadays education is growing more rapidly and more complex, education problems faced is not a challenge that is left alone, but it requires constructive thinking in order to achieve the quality of the goal of good education. The problems in question include the competence of teaching teachers because teachers as people who deal directly with learners should have good competence in the implementation of teaching and learning process. Learning takes place in human life because of the interaction between two or more people, the interaction between two or more people, the interaction between two or more people, the interaction that involves the exchange of information that is unknowingly done in our daily lives. So that learning reinforces through experience. Learning has a charge that involves two or more people. Learning takes place as long as each individual builds mutually agreeable and satisfying cooperation. Learning is strived to provide interaction and communication that ensures the common good so that in the learning can be a mutually ripe process. Learning as a process is done by the individual to gain a whole new behavioral change, as a result of the individual's own practice in his interaction and environment. Learning is different from Teaching, learning does not have English roots. Learning is different from learning. Therefore learning if translated into English learningization is the efforts of educators to make learners learn (to makes people or student learn). In every lesson effective conditions must be planned and cultivated by the teacher deliberately in order to avoid adverse conditions (prevention efforts), and restore optimal conditions in case of damaging things caused by the behavior of learners in the classroom.